Replacement of choline chloride with natural choline in broiler chicken diets - Iglesias, Bernardo Fabricio; Charriere, Maria Viviana; Fain Binda, Virginia; Pinto, Silvina; Vicente, Gonzalo; Vagedes, Christian (Poultry & Egg Association, 2025)
Poster y resumen